PECULIARITIES OF THE SOIL COVER WITHIN THE EARTH'S TECTONICALLY ACTIVE ZONES - I. S. Mikhailov (Бюллетень Почвенного института им. В.В. Докучаева, 2012)
Under study are endogenic and exogenic pseudosoil formations within the tectonically active regions of the Earth. Red-colored clayey formations, saprolites, carbonate crusts and horizons, salt formations are considered as endogenic formations while mud flows and cryogenic formations - as exogenic ones. Several formations in tectonically active regions, which have been related to the soil cover prove to be pseudosoil formations.